2019
DOI: 10.7717/peerj.6738
|View full text |Cite
|
Sign up to set email alerts
|

Examining the assumptions of heterogeneity-based management for promoting plant diversity in a disturbance-prone ecosystem

Abstract: Background Patch-burn management approaches attempt to increase overall landscape biodiversity by creating a mosaic of habitats using a patchy application of fire and grazing. We tested two assumptions of the patch-burn approach, namely that: (1) fire and grazing drive spatial patch differentiation in community structure and (2) species composition of patches change through time in response to disturbance. Methods We analyzed species cover data on 100 m2 square quadrats from 128 sites located on a 1 × 1 km U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Further, we only used cattle, and even if cattle are supposed to have similar effect on the vegetation as bison (Towne et al, 2005), other herbivore species and types also need to be tested. Previous studies have demonstrated the complexity of fire-herbivory interactions, and some of these studies have even shown negative effects of fire and herbivory on biodiversity (McGlinn & Palmer, 2019;McGranahan, Engle, et al, 2013;Scasta et al, 2016). Further research is therefore needed to understand how different fire regimes, such as variation in fire frequency, seasonality, and intensity, and also grazing regimes, such as herbivory type, and animal density, affect the ecosystem and also how they interact in a temperate European ecosystem.…”
Section: Implications For Biodiversity Management Of Open Ecosystemsmentioning
confidence: 99%
“…Further, we only used cattle, and even if cattle are supposed to have similar effect on the vegetation as bison (Towne et al, 2005), other herbivore species and types also need to be tested. Previous studies have demonstrated the complexity of fire-herbivory interactions, and some of these studies have even shown negative effects of fire and herbivory on biodiversity (McGlinn & Palmer, 2019;McGranahan, Engle, et al, 2013;Scasta et al, 2016). Further research is therefore needed to understand how different fire regimes, such as variation in fire frequency, seasonality, and intensity, and also grazing regimes, such as herbivory type, and animal density, affect the ecosystem and also how they interact in a temperate European ecosystem.…”
Section: Implications For Biodiversity Management Of Open Ecosystemsmentioning
confidence: 99%
“…As such, pyric herbivory can increase ecosystem heterogeneity (Fuhlendorf & Engle, 2004; McGranahan et al., 2012; Winter et al., 2012). This resulting heterogeneity ultimately increases biodiversity by varying effects on vascular plant species and life‐form composition (Collins, 1992; Fuhlendorf & Smeins, 1999; Kirkpatrick et al., 2016; McGlinn & Palmer, 2019). Previous work has shown an increase in graminoids and a decrease in woody species under herbivory and fire (Fuhlendorf & Engle, 2004; Herrera et al., 2021; Pekin et al., 2012; Van Uytvanck & Hoffmann, 2009).…”
Section: Introductionmentioning
confidence: 99%